2013
DOI: 10.15448/1983-652x.2013.2.13143
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da oxidação de óleos, gorduras e azeites comestíveis em processo de fritura

Abstract: Avaliar a oxidação e a estabilidade de óleos e azeites utilizados na fritura. Foram determinados os índices de acidez, peróxido, iodo, refração e oxidação. Materiais e Métodos: Os experimentos foram conduzidos com frituras de batatas durante 20 e 45 min (180ºC) empregando os óleos de girassol (OG), milho (OM), óleo de canola (OC), soja (OS), os azeites de oliva (AO) e extra virgem (AOEV) e as gorduras de palma (GP) e vegetal hidrogenada (GVH). Os dados foram analisados utilizando-se uma análise de variância se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
5
Order By: Relevance
“…The residual oil from agroindustry follows several processes, including centrifugation at high temperature and rotation, resulting in the modification in the physical and chemical characteristics; the oil then becomes dark, viscous, with an unpleasant odor, and consequently with a high index of peroxides. Rios et al (2013) evaluated the oxidation process of frying oil by the peroxide index at different times, and the authors observed an index variation from 1.38 mEq. kg -1 to 9.96 mEq.kg -1 after 4 h, showing that heating is an important parameter in the oil oxidation process.…”
Section: Experimental Designmentioning
confidence: 99%
“…The residual oil from agroindustry follows several processes, including centrifugation at high temperature and rotation, resulting in the modification in the physical and chemical characteristics; the oil then becomes dark, viscous, with an unpleasant odor, and consequently with a high index of peroxides. Rios et al (2013) evaluated the oxidation process of frying oil by the peroxide index at different times, and the authors observed an index variation from 1.38 mEq. kg -1 to 9.96 mEq.kg -1 after 4 h, showing that heating is an important parameter in the oil oxidation process.…”
Section: Experimental Designmentioning
confidence: 99%
“…Os peróxidos nem sempre são bons indicadores, pois são instáveis, formamse rápido e também são fracionados em moléculas menores, aldeído e cetona, que algumas vezes não são encontradas na análise (RIOS, 2013).…”
Section: Resultsunclassified
“…Research, Society and Development, v. 10, n. 3, e32210313408, 2021 (CC BY 4. When vegetable oil is subjected to a heating or frying process, the temperature directly influences the oxidation reaction causing the rate of peroxides formation to be less than the degradation. Thus, the peroxide index is not a good quality indicator of vegetable oils that have undergone heating, but it can be used for olive oil, since its predominant fatty acid is oleic, being less susceptible to oxidation reactions (Houshia et al;2019, Rios, Pereira & Abreu, 2013.…”
Section: Olive Oil Quality and Identity Parametersmentioning
confidence: 99%